Analisis Kemampuan Using Symbolic, Formal and Technical Language and Operation Dan Representation Siswa SMPN 4 Kota Bengkulu - Stiadi, Elwan (Universitas Sebelas Maret, 2025)
Based on the results of PISA, Indonesian students' mathematical literacy process skills—particularly in the aspects of representation and using symbolic, formal, and technical language and operations—are still relatively low. This study aimed to analyze students' abilities in mastering the components of the PISA mathematical literacy process. The research employed a descriptive method. The subjects were students of classes IX-1 and IX-2 at SMP Negeri 4 Kota Bengkulu during the odd semester of the 2021/2022 academic year. The instruments and data collection techniques used in this study included test sheets and interviews. The results showed that 45.45% of students demonstrated proficiency in the representation process, while 49.82% showed ability in using symbolic, formal, and technical language and operations. These results indicate that less than 50% of students in classes IX-1 and IX-2 of SMPN 4 Kota Bengkulu possess adequate skills in these two aspects. Therefore, these abilities still need to be improved.Berdasarkan hasil PISA, kemampuan proses literasi matematika siswa Indonesia dalam aspek representation dan using symbolic, formal and technical language and operation masih tergolong rendah. Penelitian ini bertujuan untuk menganalisis kemampuan siswa dalam menguasai komponen proses literasi matematika PISA. Penelitian ini merupakan penelitian deskriptif (Descriptive Research). Subjek dalam penelitian ini adalah siswa kelas IX 1 dan IX 2 SMP Negeri 4 Kota Bengkulu semester ganjil tahun ajaran 2021/2022. Instrumen dan teknik pengumpulan data yang digunakan dalam penelitian ini adalah lembar tes dan wawancara. Hasil penelitian menunjukkan bahwa, kemampuan proses siswa dalam menyelesaikan soal literasi matematika PISA 2012 sebanyak 45,45% siswa memiliki kemampuan proses representation dan sebanyak 49,82% siswa memiliki kemampuan proses using symbolic, formal and technical language and operation. Hasil ini menunjukkan bahwa kurang dari 50% siswa kelas IX 1 dan IX 2 SMPN 4 Kota Bengkulu memiliki kemampuan representation dan using symbolic, formal and technical language and operation. Oleh karena itu, kemampuan tersebut masih perlu ditingkatkan.